Gelfand local Bezout domains are elementary divisor rings - Zabavsky, B.V.; Pihura, O.V. (Carpathian Mathematical Publications, 2015)
We introduce the Gelfand local rings. In the case of commutative Gelfand local Bezout domains we show that they are an elementary divisor domains.